2017
DOI: 10.1080/10807039.2017.1387476
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of trace metals in Mediterranean mussels (Mytilus galloprovincialis) from a fish farm with copper-alloy mesh pens and potential risk assessment

Abstract: Concentrations of trace metals were determined in the muscle tissue, digestive gland and gills of Mediterranean mussels (Mytilus galloprovincialis) collected from different locations around an offshore copper alloy fish farm. Levels of copper (Cu), zinc (Zn), manganese (Mn) and iron (Fe) as mg/kg wet weight in the edible part of the mussels collected from distant zone (upstream Zn7.33 > Fe2.8 > Cu0.13 > Mn0.07 and downstream Zn9.9 > Fe5.67 > Cu0.18 > Mn0.17) were significantly lower (p < 0.05) than those sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Even if HQs were below the critical value 1, so no possible risks are associated with mussel consumption collected from the study areas, we noted the case of lead which registered the highest calculated HQs from all heavy metals: 0.2 in A1, 0.03 in A3, 0.012 in A2, respectively. Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 92%
“…Even if HQs were below the critical value 1, so no possible risks are associated with mussel consumption collected from the study areas, we noted the case of lead which registered the highest calculated HQs from all heavy metals: 0.2 in A1, 0.03 in A3, 0.012 in A2, respectively. Our results are in accordance with findings of other studies conducted in order to assess potential human risks associated with mussel consumption in the region of Black Sea [54][55][56]. It should be noted also that calculated hazard quotients for investigated heavy metals within the current research were higher than values found in other investigated food categories in Romania (honey, food supplements) [57,58].…”
Section: Estimated Risk Through Mussel Consumptionsupporting
confidence: 92%
“…Many authors had reported the high aptitude of two mussel organs gill and digestive gland in the storage process of heavy metals as Viarengo et al (1990), Sreedevi et al (1992), Amiard et al (1993), Stien et al (1998), Blasco and Puppo (1999), Vlahogianni et al (2007), Peyrot et al (2009), Cooper et al (2010, Giarratano et al (2011), Jebali et al (2014, Belcheva et al (2015), Chandurvelan et al (2015), and Yigit et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…are the most commonly used bioindicator species in marine pollution monitoring, with highly developed bioaccumulation ability [1][2][3]. As filter-feeding organisms, mussels accumulate a wide range of contaminants from their environment, including different trace metals, microplastics (MPs), pharmaceuticals, pesticides, and other sorts of emerging contaminants [4][5][6][7][8][9][10]. They are also known for their bioconcentration ability, since they cannot regulate individual concentrations of metals [11] or other pollutants, for instance, MPs [9].…”
Section: Introductionmentioning
confidence: 99%